Sinergisitas Komunikasi Antarbudaya dalam Pembelajaran Bahasa Inggris di Tingkat Universitas - Gusti Ayu Putu Diah Permata Sari AR; Ketut Yuniati (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2022)
Nowadays, English lesson becomes important subject that has been taught for all educational sectors. Learning English was not only focuses in improving four essential skills (speaking skill, listening skill, reading skill, and writing skills) but also it was needed to understand the cultural aspects. Regarding the phenomenon, this article described the synergisity of intercultural communication in English teaching and learning process at University. The introduction of target language culture would be helped the students to improve the language skills. Furthermore, by discovering the language culture could minimize the students’ interference during the communication. In the English lesson, university students are expected to be able to find the cultural material which suitable with English material. English lecturer could support that activity by providing English text that is written by native writer and showed the real phenomena in those areas. Besides, table manner activity helped the students to catch the tradition of western culture about cutlery, technique and also dining etiquette. The conversation practice with native speaker could also increase the student ability in speaking skill. Thus, the students were able to respect the world’s culture through intercultural communication.